Cross-National and Religious Relationships With Posttraumatic Growth: The Role of Individual Differences and Perceptions of the Triggering Event - Taku, Kanako (Journal of cross-cultural psychology, 2014)
Posttraumatic growth (PTG)—positive changes experienced as a result of psychological struggle with highly challenging life circumstances—generally correlates with greater religiosity and optimism, and often shows gender and cross-national differences. The current study examined the relationship of national background and religion with PTG, as well as individual differences variables (i.e., optimism, pessimism, and gender) and individuals’ appraisal or perceptions of the event (i.e., whether the event was perceived as having a direct or indirect impact, and whether the event was perceived as deliberate or accidental). American and Japanese college students identified a highly stressful life event and completed the PTG Inventory and the revised Life Orientation Test. Results showed that national background and religiosity (religious affiliation and strengths of religious beliefs) predicted the level of overall PTG. In addition to the national and religious associations, gender and optimism had positive associations with PTG. The role of individual differences variables and perceptions of the triggering event varied cross-nationally across the PTG domains. Limitations and future directions are discussed.